-23=-2(x+1)+9

Simple and best practice solution for -23=-2(x+1)+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -23=-2(x+1)+9 equation:


Simplifying
-23 = -2(x + 1) + 9

Reorder the terms:
-23 = -2(1 + x) + 9
-23 = (1 * -2 + x * -2) + 9
-23 = (-2 + -2x) + 9

Reorder the terms:
-23 = -2 + 9 + -2x

Combine like terms: -2 + 9 = 7
-23 = 7 + -2x

Solving
-23 = 7 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-23 + 2x = 7 + -2x + 2x

Combine like terms: -2x + 2x = 0
-23 + 2x = 7 + 0
-23 + 2x = 7

Add '23' to each side of the equation.
-23 + 23 + 2x = 7 + 23

Combine like terms: -23 + 23 = 0
0 + 2x = 7 + 23
2x = 7 + 23

Combine like terms: 7 + 23 = 30
2x = 30

Divide each side by '2'.
x = 15

Simplifying
x = 15

See similar equations:

| 3y^2-12y+8=0 | | 43-8c=5 | | S=4*3.14r^2 | | 3250x^2+5489x+5212=91000 | | 3/k=4/5 | | z/2+26=17.5 | | 3x+2x-10x-(-4x)=13 | | .5x+2= | | 3x+2x-10u-(-4u)=13 | | 10=-4x+3x^2 | | -4x+4y=1 | | 6+2x^2-3x=8x^2 | | 4y=12x-2xy | | 10x^2-6=9x | | f(x)=10-12 | | 10x-29=4x+7 | | f(5)=10-12 | | 18x-15=-2x+25 | | 15x-10=5x+10 | | 42+3c=56 | | 8(x-4)+4=8x-4(4-x) | | f(5)=2x-12 | | 64*8/2x | | 5y^2+6y= | | 2(F-4)=-22 | | 6+2ln(x)=20 | | f(x)=9-6/x | | 0.6(5x+10)=1.6-(x+2) | | 2n-(n/2)=9 | | 3(2x-6)-3=3(x-3)-3 | | (x+4)(2x+3)=117 | | 4y+6x=14 |

Equations solver categories